TEACHING LISTENING COMPREHENSION: An Interim Report on a Project to Use Uncontrolled Language Data as a Source Material for Training Foreign Students in Listening Comprehension. - Stanley, John A. (TESOL Quarterly, 1978)
The article presents a report on a project regarding the use of an unscripted recorded material for teaching listening comprehension to foreign students. One of the features of the unscripted recorded material is its range of variation in terms of pace. Some people speak slowly and some people speak quickly, so pacing may reflect attitudes of speakers. Pacing may also reflect the amount of common knowledge shared by a speaker and a listener. It is significant for teachers to explain the difference between the perceptual importance of parallel processing and phoneme variability to language learners. The parallel processing and phoneme processing influence the encoding process of a listener. Other comprehension difficulties are caused by the phenomena of assimilation, vowel reduction, elision and consonant deletion.